Handbook for sound engineers - Ballou, Glen M. (Amsterdam [u.a.] Elsevier, Focal Press, 2008)
Handbook for Sound Engineers is the most comprehensive reference available for audio engineers. All audio topics are explored: if you work on anything related to audio you should not be without this book! The 4th edition of this trusted reference has been updated to reflect changes in the industry since the publication of the 3rd edition in 2002 -- including new technologies like software-based recording systems such as Pro Tools and Sound Forge, digital recording using MP3, wave files and others, mobile audio devices such as iPods and MP3 players. Over 40 topics are covered and written by many of the top professionals for their area in the field, including Glen Ballou on interpretation systems, intercoms, assistive listening, and image projection, Ken Pohlmann on compact discs and DVDs, David Miles Huber on MIDI, Dr. Eugene Patronis on amplifier design and outdoor sound systems, Bill Whitlock on audio transformers and preamplifiers, Pat Brown on fundamentals and gain structures, Ray Rayburn on virtual systems and digital interfacing, and Dr. Wolfgang Ahnert on computer-aided sound system design and acoustics for concert halls. * Condenses years of information and technology into one source * Contributors are the leading experts in their fields * Reflects current practice covering all the fundamental aspects of sound engineering
Fundamentals of Audio and Acoustics; Psychoacoustics and Perception; Acoustical Noise Control; Acoustical Treatment for Indoor Areas; Acoustics for General Purpose Rooms; Acoustics for Auditoriums and Concert Halls; Acoustics for Stadiums and Outdoor Venues; Acoustics for Cinemas; Modelling and Auralization; Resistors, Capacitors, and Inductors; Audio Transformers and their Uses; Tubes, Discrete Solid-State Devices, and Integrated Circuits; Heat Sinks and Relays; Transmission Techniques -- Wire; Microphones; Loudspeakers, Enclosures, and Headphones; Loudspeaker Cluster Design; Power Supplies; Amplifier Design; Preamplifiers and Mixers; Atenuators; Filters and Equalizers; Delay; Mixing Consoles; VI Meters and Devices; Disk Recording and Playback; Magnetic Analog and Digital Recording and Playback; MIDI; Compact Discs, DVD Audio and Video, SACD and other Digital Media; DSP Technology; Grounding; Gain Structures; Sound System Design; Computer-Aided Sound System Design; Designing for Speech Intelligibility; In-Ear Monitoring; Virtual Systems; Digital Audio Interfacing and Networking; Complete Interpretation Systems; Assistive Listening Systems; Intercoms; Image Projection; Dolby Surround and Dolby Digital; Audio Measurements; Fundamentals and Units of Measurements; Loudspeakers; Loudspeaker Cluster Design; Preamplifiers and Mixers; Analog Consoles and Systems; Digital Consoles; Compact Discs, DVD Audio and Video, SACD and other Digital Media; MIDI; Sound System Design; Designing a Sound System with a Computer; Gain Structures; Grounding; Virtual Systems; Digital Audio Interfacing and Networking; Designing for Speech Intelligibility; Modelling and Auralization; Dolby Surround Sound; Audio Measurements; Digital Media; Fiber Optic Transmission; Intelligibility.
Includes bibliographical references and index
Previous ed.: Amsterdam; London: Elsevier/focal, 2002
Keywords: Acoustical engineering -- Handbooks, manuals, etc; Sound -- Recording and reproducing -- Digital techniques; Acoustical engineering -- Handbooks, manuals, etc; Sound -- Recording and reproducing -- Digital techniques